Propagation studies on rain for 5.8 GHz and 23 GHz point to point terrestrial link - Kesavan, U.; Tharek, A.R.; Rahim, S.K.A.; Islam, Md. Rafiqul (IEEE, 2012)
The radio waves propagating through the earth atmosphere will be attenuated due to the presence of atmosphere particles, such as water vapor, water drops and the ice particles. The atmospheric gases and rain will both absorb and scatter the radio waves, and consequently degrade the performance of the link. Rain is a major source of attenuation for microwave propagation above 7 GHz. In tropical and equatorial regions, the rain intensity is higher and designing terrestrial and earth-to-satellite microwave links are very critical and challenging for high frequencies. This paper presents the summary of rain effects studies for lower operating frequency such as C band compare to higher operating frequency such as Ka band in tropical environment. The main objective to justified the literature findings on the effect of rain at lower and higher operating frequency in microwave link and solution to overcome it. An experimental test bed has been set up for 5.8 GHz and 23 GHz terrestrial point to point data communication link. The received signal strength (RSS) data and rain fall intensity data were recorded for 24 hours daily over period of 7 months June 2011 – Dec 2011) at 1 minute interval. The collected rain rate data been analyzed with some prediction based on the results obtain. The main outcome of the research shows there is no effect of rain for 5.8 GHz link but there is strong effects with rain on the 23 GHz link. It was observed 15 dB to 35 dB attenuation during measurement period. This will be useful resources of information for researchers or telecommunication engineers, before implementation any mitigation method as a solution for point to point terrestrial link communication in future.